Resettling Refugees through Community Sponsorship: A Revolutionary Operational Approach Built on Traditional Legal Infrastructure - Bond, Jennifer; Kwadrans, Ania (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2019)
More than a dozen states are exploring the potential of introducing community sponsorship programs as a way of contributing to the global refugee protection regime. This article provides a comparative analysis of the legal and administrative frameworks that have underpinned the introduction of community sponsorship in four diverse countries: Canada, the United Kingdom, New Zealand, and Argentina. We also briefly examine the introduction of co-sponsorship in the United States, a country without any formal national program. We conclude that while community sponsorship programs have the potential to revolutionize refugee resettlement, their operationalization is not contingent on revolutionary legal infrastructure.